PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 016 BULUH KASAP - Listono, Agus Listono; Alpusari, Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract. This research was motivated by the low haasil social studies students, with an average grade of 62.5. While the value of minimum completeness criteria (KKM) IPS is 65 Among students who were 23 people only 14 people who achieve mastery klasifikal KKM with 43.75% .penelitian is penelitaian class action (PTK) were enacted aimed at improving student learning outcomes IPS SDN 016 fourth grade coarse fur with implementing cooperative learning model think-pair-share (TPS). formulation of the problem: if the application of cooperative learning model think-pair-share (TPS) can improve learning outcomes IPS Elementary School fourth grade students coarse reed 016. This study was carried out on the 2nd d of April 2014 to the mai 07, 2014 with 2 siklus.subjek this study were fourth grade students of SDN 016 C feather kasab who are 32 students who d make data.instrumen source of data collection in this thesis is the activity sheet for Master and students and learning outcomes. This thesis presents the results of the study were obtained daily before action replay value with an average of 62.5 increase in the first cycle with the average being 64.8.pada increase the second cycle with an average of 73.28 .aktifitas teacher in the learning process in the cycle I first encounter the second meetings of 54.17% .and menjadi62,6%. Cycle II first meeting and the second meeting of 70.83% increased to 79.17% The results of the study in class IV SDN 016 fleece kasab prove that the application of cooperative learning model type of think-pair-share (TPS) can improve learning outcomes IPS grade IV C SDN 016 coarse fur. Keywords: learning mode Think Pair Share (TPS), the results of social studies.